2021
DOI: 10.1038/s41598-021-98133-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel ternary ZIF-8/GO/MgFe2O4 nanocomposite and its application in drug delivery

Abstract: In recent year, metal–organic frameworks (MOFs) have been displayed to be a category of promising drug delivery systems because of their crystalline structure, the potential of further functionality, and high porosity. In this research, graphene oxide was synthesized from pure graphite via hummer method and then MgFe2O4 nanoparticles was incorporated into the synthesized ZIF-8 metal–organic frameworks which followed with loading on the surfaces of graphene oxide. In continue, tetracycline as an antibiotic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…We provided Table 2 to show a comparison between our research with similar studies. 37,45–48 As can be seen, the newly prepared nanocomposite including NiFe 2 O 4 @MIL-101(Fe)/GO had a satisfactory drug loading percentage, drug release, and also antibacterial activities in comparison with previous structures.…”
Section: Resultsmentioning
confidence: 81%
“…We provided Table 2 to show a comparison between our research with similar studies. 37,45–48 As can be seen, the newly prepared nanocomposite including NiFe 2 O 4 @MIL-101(Fe)/GO had a satisfactory drug loading percentage, drug release, and also antibacterial activities in comparison with previous structures.…”
Section: Resultsmentioning
confidence: 81%
“…The FTIR spectrum of pure TC is shown in Figure a, and the corresponding peaks due to the presence of OH and NH 2 groups are observed at 3353 cm –1 . In addition, the peak at 3041 cm –1 is attributed to the C–H stretching vibrations of aromatic rings, the peaks from 1572 to 1620 cm –1 are attributed to CC stretching, the peak at 1214 cm –1 is attributed to C–N stretching, the peak at 1630 cm –1 is attributed to CO stretching, and the peaks from 1037 to 1113 cm –1 are attributed to C–O stretching. , In addition, in the FTIR spectrum of TC–Ca–Sr–MOF, the peaks with strong vibrational bands at approximately 1601, 1510, and 1396 cm –1 , which are attributed to CO, C–O, and C–H vibrations, confirm the presence of the bridge coordination mode of Ca and Sr metal carboxylates in the MOF structures. The absorption band at 3308 cm –1 is attributed to the NH 2 moiety of TC, indicating the successful loading of TC onto the Ca–Sr–MOF structure. , Moreover, in the FTIR spectrum of TC–Ca–Sr–AMN–MOF, absorption bands are noted at approximately 1598 and 1451 cm –1 , which are attributed to CO and C–H vibrations, and an absorption band is noted at approximately 1024 cm –1 , which is attributed to the weak aliphatic amine bond (C–N) of AMN .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, MIC values obtained were 0.1 μg mL −1 for E. coli and 1.6 μg mL −1 for S. aureus . In another study, Sanaei-Rad et al 169 fabricated ZIF-8/GO/MgFe 2 O 4 consisting of Mg 2+ , Zn 2+ and 2-methyl imidazole for tetracycline transport. The achieved results showed that 92% tetracycline was released at pH 7.4.…”
Section: Mof-based Carriers In Drug Delivery Systemsmentioning
confidence: 99%